(untitled) - Barney, Jay B. (New York, 1997)
Dealing with competitive advantage in business, this work develops a framework that emphasizes the importance of understanding not only the threats and opportunities in a firm's competitive environment, but also the implications of firms' organizational strengths and weaknesses.
Keywords: Industrial management,Strategic planning,Quản lý công nghiệp,Kế hoạch chiến lược